Promoting Ethylene Selectivity from CO2 Electroreduction on CuO Supported onto CO2 Capture Materials. Issue 5 (15th February 2018) - Yang, Hui‐Juan; Yang, Hong; Hong, Yu‐Hao; Zhang, Peng‐Yang; Wang, Tao; Chen, Li‐Na; Zhang, Feng‐Yang; Wu, Qi‐Hui; Tian, Na; Zhou, Zhi‐You; Sun, Shi‐Gang
Abstract: Cu is a unique catalyst for CO2 electroreduction, since it can catalyze CO2 reduction to a series of hydrocarbons, alcohols, and carboxylic acids. Nevertheless, such Cu catalysts suffer from poor selectivity. High pressure of CO2 is considered to facilitate the activity and selectivity of CO2 reduction. Herein, a new strategy is presented for CO2 reduction with improved C2 H4 selectivity on a Cu catalyst by using CO2 capture materials as the support at ambient pressure. N‐doped carbon (N x C) was synthesized through high‐temperature carbonization of melamine andl ‐lysine. We observed that the CO2 uptake capacity of N x C depends on both the microporous area and the content of pyridinic N species, which can be controlled by the carbonization temperature (600–800 °C). The as‐prepared CuO/N x C catalysts exhibit a considerably higher C2 H4 faradaic efficiency (36 %) than CuO supported on XC‐72 carbon black (19 %), or unsupported CuO (20 %). Moreover, there is a good linear relationship between the C2 H4 faradaic efficiency and CO2 uptake capacity of the supports for CuO. The local high CO2 concentration near Cu catalysts, created by CO2 capture materials, was proposed to increase the coverage of CO intermediate, which is favorable for the coupling of two CO units in the formation of C2 H4 . This study demonstrates that pairing Cu catalysts with CO2 capture supports is a promising approach for designing highly effective CO2 reduction electrocatalysts. Abstract : The higher the better : CuO supported on N‐doped carbon, a CO2 capture material, exhibits high faradaic efficiency for CO2 electroreduction. The higher CO2 uptake capacity, the higher C2 H4 selectivity. The local high CO2 concentration near the Cu catalysts, created by the CO2 capture materials, is proposed to increase the coverage of CO intermediate, which is favorable for the coupling of two CO units in the formation of C2 H4 .